A First Estimate of the Annual Prevalence of Basivertebral Nerve Ablation Candidates in a Spine Clinic. Issue 11 (2nd June 2022) - Sherwood, David; Miller, Scott; Epps, Adam; Gill, Benjamin; Zhivotenko, Oksana; Khan, Samir; Swenson, Theodora; Gardner, James; Roehmer, Christian; Martin, Dann; Kennedy, David "D J"; Modic, Michael; et al.
Abstract: Background: Emerging literature supports the use of basivertebral nerve ablation (BVNA) for a specific cohort of patients with chronic low back pain and Type 1 or Type 2 Modic changes from vertebral levels L3–S1. The early literature warrants further evaluation. Studies establishing the efficacy of BVNA use highly selective patient criteria. Objective: Provide a first estimate of the prevalence of BVNA candidates in a spine clinic over a year using the foundational studies patient selection criteria? Methods: A retrospective review of four fellowhsip trained spine physiatrists patient encounters at a large academic medical center using relevant ICD-10 codes to isolate chronic low back pain without radiating symptoms from January 1, 2019 to January 1, 2020. Charts were then reviewed by a team of physicians for exclusionary criteria from the foundational studies which have demonstrated benefit from BVNA. MRI's from qualifying charts which did not meet exclusionary criteria were then independently reviewed by four physician for localization and characterization of Modic changes. Results: The relevant diagnostic codes query yielded 338 unique patient records. Based on exclusionary criteria or lack of imaging availability, 318 charts were eliminated. The remaining 20 charts qualified for imaging review. There were 11 charts in which there was 100% agreement between all reviewers regarding the presence and either Type 1 or Type 2 Modic changes between vertebral levels L3 to S1. Accordingly, the prevalence of eligibility for BVNA was 3% (11/338, 95% CI 1–5%). Conclusion: The population which may benefit from BVNA is small. Our study demonstrated that over a year, the prevalence for BVNA candidacy using the foundational studies criteria was 3% (95% CI 1% – 5%). While physicians may be tempted to use less stringent selection criteria in practice, upon doing so they cannot cite the foundational studies as evidence for the outcomes they expect to achieve. Those outcomes will require more studies which formally assess the benefits of BVNA when selection criteria are relaxed.